Evaluating new concepts of PSS based on the customer value: Application of ANP and niche theory. Issue 9 (1st June 2015) - Lee, Sora; Geum, Youngjung; Lee, Sungjoo; Park, Yongtae
Highlights We propose a method for evaluating product service systems (PSS) concept. The method is based on perceived value through the customer experience cycle. We compare customer acceptability of new PSS concepts with existing products. The ANP and niche theory were adopted to quantify customer's perceptions. A case study on car sharing has verified the feasibility of the proposed method.